Genetic improvement and related activities. Regional activities. IVT-CIAT collaboration - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1987)
CIAT has a collaborative bean breeding project with the Institute for Horticultural Plant Breeding in the Netherlands. In 1986 research was concentrated on incorporating resistance to BCMV into CIAT-bred lines. Testing for beans resistant to the BCMV-Tn strain continued. Selections came from the 1st, 2nd, and 3rd crossing generations derived from CIAT lines x IVT 7620 (an interspecific cross with Phaseolus coccineus with resistance to BCMV and BYMV, including the Tn strain). Excellent resistance to BYMV was selected in the 1st crossing generation between CIAT breeding lines and IVT DEL 35 013035 ADD 35 CIAT tiene un proyecto colaborativo de mejoramiento de frijol con el Institute for Horticultural Plant Breeding en los Paises Bajos. En 1986 la investigacion se concentro en la incorporacion de resistencia a BCMV en lineas mejoradas del CIAT. Continuan las pruebas para resistencia del frijol a la cepa BCMV- Tn. Las selecciones provenian de los cruzamientos de la primera, segunda y tercera generaciones derivadas de lineas CIAT x IVT 7620 (cruzamiento interespecifico con Phaseolus coccineus con resistencia a BCMV y BYMV, incluyendo la cepa Tn). Se selecciono resistencia excelente a BYMV en la generacion del primer cruzamiento entre lineas mejoradas del CIAT y IVT 7620. (CIAT)